Clinical, histological, immunological presentations and outcomes of bullous systemic lupus erythematosus: 10 New cases and a literature review of 118 cases - de Risi-Pugliese, Tullia; Cohen Aubart, Fleur; Haroche, Julien; Moguelet, Philippe; Grootenboer-Mignot, Sabine; Mathian, Alexis; Ingen-Housz-Oro, Saskia; Hie, Miguel; Wendremaire, Noémie; Aucouturier, Françoise; Lepelletier, François; Miyara, Makoto; et al. (Seminars in arthritis and rheumatism, 2018)
Bullous systemic lupus erythematosus (BSLE) is a rare blistering condition associated with systemic lupus erythematosus (SLE). We conducted a multi-center retrospective study and literature review in order to describe the clinical, immunological, and histological presentations and outcomes of BSLE. The skin biopsies were centrally reviewed, and sera obtained during a flare of BSLE were analyzed for identification of circulating anti-basement membrane zone antibodies. Ten patients (all women, median age at SLE diagnosis of 22 years) were included, as well as 118 cases from a systematic review of the literature. Lupus nephritis was associated in 50% of the cases. BSLE presented as tensed bullae on normal or erythematous skin, predominantly localized on the trunk, arms, head, and neck. Urticarial lesions were associated in 31% of the cases, and mucous membrane involvement was seen in 51%. Histological analyses displayed subepidermal detachment, dermal infiltration of polynuclear neutrophils, alignment of these cells at the basal membrane zone and leukocytoclasis. The direct immunofluorescence was polymorphic, showing linear and/or granular deposits of IgG, IgA, IgM, and/or C3. Anti-type VII collagen antibodies were detected in 69% of cases. Dapsone was efficacious in 90% of cases. BSLE is rather an autoimmune neutrophilic blistering disease associated with SLE than a cutaneous manifestation and may be associated with active extra-cutaneous manifestations of SLE. Dapsone is the first-choice option.